Integrated Planning for Sustainable Development of Kuttanad Wetland Region, Kerala State. (2016) - Kumar, Sanil; Devadas, V.
Abstract: The planning process for Wetland Regions is often considered under regional plans and often involves a team of consultants including urban planners, environment engineers and representations from various departments. Their role in the ecological and environmental well-being of any living system is unparalleled. With increasing urbanization, the limits of these regions are often affected with increased human habitations coming up in such sites including the example of Kuttanad wetland region. Their isolated planning process often could lead to worsening of existing situation or newer challenges paving ways for possible disasters. The paper examines the present situation in Kuttanad Region and discusses similar situations in the Indian and global context. It also recommends the systems approach for problem mapping and suggests possible recommendations for sustainable planning. In the light of climate change and increased awareness about sustainability, one can utilize planning as a tool to integrate 'aspirations for growth' as a decisive measure for the planning of cities and analyse it utilizing existing mechanisms for planning without suggesting drastic overhaul of the existing system.